2009
DOI: 10.1021/cm803322d
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Silver Molybdenum Oxyfluoride Perovskite as a Cathode Material for Lithium Batteries

Abstract: Novel electroactive nanostructured silver molybdenum oxyfluoride (SMOF) perovskites Ag1+ 3Mo6+(O3F3) have been successfully synthesized by a mechanochemical reaction. The formation of this perovskite was investigated throughout the Ag−Mo composition range with the use of either Ag1+ or Ag2+ in the form of AgF and AgF2 as the reactant, respectively. The compositional study combined with X-ray diffraction and extensive Raman investigation was utilized to determine structure and cation distribution and infer oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
5
36
0
Order By: Relevance
“…As described in the previous paper [7], the SMOF perovskite remained as the significant phase in a wide range of AgF-MoO 3 compositions (x = 1. [5][6][7][8][9]. Consistent with the idealized stoichiometry, the maximum phase intensity of the perovskite is obtained at x = 3 relative to the minimal quantity of Mo-or Agcontaining minor phases.…”
Section: Smof Perovskite-physical Characterizationsupporting
confidence: 61%
See 3 more Smart Citations
“…As described in the previous paper [7], the SMOF perovskite remained as the significant phase in a wide range of AgF-MoO 3 compositions (x = 1. [5][6][7][8][9]. Consistent with the idealized stoichiometry, the maximum phase intensity of the perovskite is obtained at x = 3 relative to the minimal quantity of Mo-or Agcontaining minor phases.…”
Section: Smof Perovskite-physical Characterizationsupporting
confidence: 61%
“…Preliminary electrochemical evaluation of SMOF electrode indicated that close to theoretical capacity of 5 inserted Li + was achieved with 3 plateaus at 3.6, 3.1 and 2.1 V when discharged to 1.5 V. Our earlier work [7] on an in situ electrochemical study by XRD suggested the insertion of the 3 Li + at the 1st plateau (>3 V) was consistent with the displacement, or possible conversion reaction, of SMOF to Ag metal. However, very little useful information Fig.…”
Section: Discharge Reaction Mechanismsupporting
confidence: 54%
See 2 more Smart Citations
“…[3] However, increasing attention has been paid to mixed-anion perovskites, such as oxyfluorides ABO 2 F and oxynitrides ABO 2 N as promising alternative materials in pigments, [4] watersplitting photocatalysis, [5] dielectric properties, [6] and cathode material. [7] Their properties arise from the substitution of oxygen with other anions as well as the fine tuning of the anionic and interacting d bands of the octahedral center B.…”
mentioning
confidence: 99%